2000
DOI: 10.1523/jneurosci.20-07-02602.2000
|View full text |Cite
|
Sign up to set email alerts
|

Brief Electrical Stimulation Promotes the Speed and Accuracy of Motor Axonal Regeneration

Abstract: Functional recovery is often poor despite the capacity for axonal regeneration in the peripheral nervous system and advances in microsurgical technique. Regeneration of axons in mixed nerve into inappropriate pathways is a major contributing factor to this failure. In this study, we use the rat femoral nerve model of transection and surgical repair to evaluate (1) the effect of nerve transection on the speed of regeneration and the generation of motor-sensory specificity, (2) the efficacy of electrical stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
689
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 737 publications
(723 citation statements)
references
References 36 publications
(45 reference statements)
31
689
1
2
Order By: Relevance
“…The regeneration rates to the tibial nerve branch (between 75-95%) two months after nerve section and suture are in good agreement with previous studies suggesting that most of the neurones have survived and regenerated to the nerve branches after the nerve injury (Fritzsch and Sonntag, 1991;Al-Majed et al, 2000), and also with findings suggesting that sensory neurons regenerate better than motoneurons (Suzuki et al, 1998;Negredo et al, 2004). A smaller proportion of sensory neurones regenerated to the skin of the third digit (59%).…”
Section: Regenerative Sproutingsupporting
confidence: 90%
“…The regeneration rates to the tibial nerve branch (between 75-95%) two months after nerve section and suture are in good agreement with previous studies suggesting that most of the neurones have survived and regenerated to the nerve branches after the nerve injury (Fritzsch and Sonntag, 1991;Al-Majed et al, 2000), and also with findings suggesting that sensory neurons regenerate better than motoneurons (Suzuki et al, 1998;Negredo et al, 2004). A smaller proportion of sensory neurones regenerated to the skin of the third digit (59%).…”
Section: Regenerative Sproutingsupporting
confidence: 90%
“…A loss of about 20 to 30% hypoglossal motoneurones (Snider and Thanedar, 1989;Törnqvist and Aldskogius, 1994) and facial motoneurones (Yu, 1988;Mattson et al, 1998) was described after cranial nerve section in adult rats. Several authors found a non-significant loss of about 10% motoneurones after sciatic nerve injury (Vanden-Noven et al, 1993;Lowrie et al, 1994;Valero-Cabré et al, 2001) and no changes with respect to the contralateral side was found after section and repair of the rat femoral nerve (Al-Majed et al, 2000).…”
Section: Labelling With the First Tracer: Neuronal Death Versus Tracementioning
confidence: 99%
“…Electrical stimulation of lesioned femoral nerve promotes regeneration of lower motor neurons [123,124]. Brief stimulation of lesioned femoral nerves for 1 hour leads to a rapid increase in messenger RNA (mRNA) levels of BDNF and its complementary high affinity receptor trkB in the motor neurons that peaks 2 days poststimulation with maximum sixfold and fourfold increases, respectively, in comparison to contralateral intact motor neurons [25].…”
Section: Intrinsic Capacity To Regeneratementioning
confidence: 99%